Akses Dan Pelayanan Transportasi Menuju Destinasi Wisata Kawasan Ekonomi Khusus (KEK) Wisata Tanjung Gunung Kabupaten Bangka Tengah - Boy Dian Anugra Sandy; Indra Gunawan (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Tanjung Gunung tourist area will be used as a Special Economic Zone (SEZ) for tourism. There are three main destinations, namely Tapak Antu Beach, Pan Semujur Beach, and Bukit Angsa Emas. The process of determining this tourism SEZ will have an impact on investment growth in Bangka Belitung. This condition is of course a driving force for investors to invest in developing tourist areas on Bangka Belitung Island. The need for tourist public transportation is important to support the smooth running of the program. With the existence of public transportation, tourist visits, both local and international, are expected to increase. This study aims to develop recommendations related to accessibility and the implementation of tourism transportation to the Tanjung Gunung tourist area. Research Methods while the analytical method uses descriptive qualitative and quantitative to determine access and transportation services to tourist destinations. From the results of the survey in the field, transportation to the area is dominated by private vehicles. Based on the analysis of transportation needs, it can be concluded that the operating time of tourist public transportation (Bus) will be carried out from 09.00 to 19.00 WITA with an average bus speed of 40 km/hour. The bus travel time is 28.5 minutes with a headway of 15 minutes. The tourism bus fleet needs are based on a calculation of 4 fleets with a capacity of 30 people.